Breaking Hagiographical Silence on Sufi Women in Medieval South Asia - Dr. Adeela Ghazanfar; Dr. Oumar saleem; Ms. Maryam Hamid (Al-Qanṭara, 2022)
Majority of the academic writings on sufis and Sufism have been restricted to hagiographical accounts of the male Sufis. A careful insight into these writings suggest that often moral standards or virtues are denoted through male and female blocks. Nonetheless sufi writings are confined to the achievements and merits of male sufis and their female counterparts remain an addendum to the original scripts. Therefore, information about sufi women and their contributions are either portrayed as peripheral quotes in the detailed stories of male sufis or described in terms of embodying male piety or female depravity. Hence, in both cases, the presence of sufi women as a distinct group is undermined and it establishes an assumed silence on the presence as well as contributions of sufi women in Sufi literature/ sufi world. However, the silence on women participation in Sufism in the Middle East, is broken with the discovery of a medieval text, Dhikr al-niswa al-muta’bbidat al-sufiyyat composed by Abu Abd al-Rahman al-Sulami (d. 1021) in the tenth century and was edited and translated from Arabic to English by Rkia Cornell in 1999. Any similar kind of manuscript has not been discovered in medieval South Asia so far which could break the ‘assumed silence’ on the presence of sufi women in medieval South Asia. In this regard, present study is an attempt to provide sufi women of South Asia a pivotal place in the historical knowledge as well as to re-establish their long-lost status in the ever-growing fabric of Sufism around the world. In the present study, silence on sufi women in South Asian context is dealt with carefully studying the historiographical as well as sufi literature of medieval times. These sources establish silence on the roles played by sufi women in medieval South Asian society whereas this article considers various genres of sufi literature to break the silence on the existence of sufi women. It also sheds light on biographical accounts of various sufi women from medieval South Asia as their names are hardly known to the world. This article attempts to breaks the silence on sufi women by providing names as well as biographical accounts for more than fifteen sufi women from the early tenth century to the start of fifteenth century. Keywords Sufi women, Sufism, Medieval South Asia, Hagiographical Silence, Malfuz, Tadhkirah, Sufi Literature